Palliative pelvic radiotherapy of symptomatic incurable rectal cancer – a systematic review - Cameron, Marte Grønlie (Informa Healthcare, 2014)
BACKGROUND. Locally advanced and recurrent rectal cancers frequently cause pelvic morbidity including pain, bleeding and mass effect. Palliative pelvic radiotherapy is used to relieve these symptoms and delay local progression. There is no established optimal radiotherapy regimen and clinical practices vary. Our aim was to review the efficacy and toxicity of palliative pelvic radiotherapy of symptomatic rectal cancer and to evaluate different fractionation schedules, based on published literature. MATERIAL AND METHODS. Systematic literature searches of Medline, Embase and Cochrane databases were performed through 2011. Studies reporting symptomatic response or quality of life (QOL) after palliative radiotherapy for rectal or rectosigmoid cancer were eligible. RESULTS. Twenty-seven studies were included, of which 23 were retrospective reviews. There were no patient-reported outcomes or QOL assessments. There were large variations in applied radiotherapy regimens. Pooled overall symptom response rate was 75% and positive responses were reported for pain (78%), bleeding and discharge (81%), mass effect (71%) and other pelvic symptoms (72%). Toxicity results were not evaluable. CONCLUSION. Palliative pelvic radiotherapy for symptomatic rectal cancer appears to provide relief of a variety of pelvic symptoms, although there is no documented optimal radiotherapy regimen in this context. There is inadequate evidence regarding onset, duration and degree of symptom palliation, QOL and associated toxicity with this treatment and prospective studies are therefore needed.